Thiol- and selenol-based peroxidases: Structure and catalytic properties - Trujillo, Madia; Tairum, Carlos A.; Oliveira, Marcos Antonio de; Soares Netto, Luis E. (Elsevier, 2022)
The three families of thiol- or selenol-based peroxidases (peroxiredoxins, Prx; glutathione peroxidases, GPx; and organic hydroperoxide resistance protein/osmotically inducible protein C, Ohr/OsmC) catalyze the reduction of hydroperoxides at the expense of thiol-containing compounds. In Prx, Ohr/OsmC, and some GPx, the catalysis involves a peroxidatic cysteine, while in other GPx, a selenocysteine. Their specificities for reducing and oxidizing substrates are distinct and may reflect their physiological roles. Prx and GPx share the thioredoxin fold common to the proteins belonging to the thioredoxin superfamily. In contrast, Ohr/OsmC present a unique barrel shape α/β fold. Some Prx change their oligomeric state under different conditions, including protein redox state, which is associated with a chaperone function. Ohr/OsmC are dimers and GPx can be monomeric or tetrameric, irrespective of their oxidation state. The mechanisms behind the extraordinary catalytic efficiency of these enzymes in the reduction of hydroperoxides are discussed.
Keywords: Catalytic mechanism; Fatty acid hydroperoxide; Glutathione peroxidase; Hydrogen peroxide; Lipoperoxidation; Organic hydroperoxide resistance protein; Peroxidase; Peroxidatic cysteine; Peroxiredoxin; Selenocysteine